Characterization of Plant Growth Promoting Endophytic Bacteria from Castor Plants [Ricinus communis (L.)] - Patel, Mrugesh M.; Joshi, Bhavesh M.; Parmar, Rudra B.; Singh, N. K.; Tapre, P. V. (International Journal of Bio-resource and Stress Management, 2022)
The present study was carried out in June–Janauary (2021–2022) at the Laboratory of the Department of Microbiology, Chimanbhai Patel College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University (SDAU), Sardarkrushinagar, Gujarat, India. 15 promising endophytic bacterial isolates from castor plants showing higher dry matter accumulation in seedlings of wheat were subjected to detailed characterization for their molecular and plant growth promoting abilities. The bacterial isolate Erc7 performed best for plant growth promoting activities viz., ammonia and IAA production, phosphate solubilization, nitrogen fixation, HCN production and antagonistic activity against Fusarium oxysporum f. sp. ricini in-vitro which cause wilt in castor plant. Pot trials involving wheat seed inoculation (rabi 2021–22) with bacterial isolates showed that the treatment with endophytic bacterial isolate Erc7 showed maximum shoot and root length (47.65 cm, 10.50 cm), shoot fresh and dry weight (824.90 mg, 308.83 mg), root fresh and dry weight (122.37 mg, 36.20 mg), spike length (09.76 cm) and number of seeds in central tiller plant-1 (15.33). PCR amplification of 16S rRNA genes and ARDRA profiling using restriction enzymes AluI, TaqI and HpaII grouped the 15 isolates in 2 clusters (A and B) at a Jaccard’s similarity co-efficient of 0.54. The best PGPR isolate Erc7 was gene sequenced for 16S rRNA gene. The sequence was submitted to the NCBI Genbank (Accession number ON514555). Upon BlastN It showed maximum similarity to Bacillus cereus. The isolates Erc7 showed presence of diplobacillus endospores which is a typical characteristic of Bacillus cereus.